Transparency International’s Report and National Election Results: Case of 14th Malaysian General Election 2018 - Hashim, Mohd Hisham; Hadi, Abdul Razak Abdul; Ibrahim, Alisa (International Journal of Psychosocial Rehabilitation, 2020)
Corruption in politics is the biggest challenge to the entire world. A myriad of local and international reports suggest that a number of politicians have attempted to frustrate the ideals of the nation state, subvert the rules of law, find and exploit loopholes in the system, and use political power to keep the executive subordinate. A study by Transparency International (TI) in 2016 concludes that one in three citizens feels that corruption is one of the biggest problems in his or her country while 53% of the respondents believe that their governments are doing poor jobs in combating corruption in the public sectors. Also, one in three citizens perceives that Member of Parliament and government officials are seen as the ‘most corrupt’ while three out of five say that big businesses and wealthy individuals have undue influence into the political processes. The objective of this study is to investigate the relationship between TI reporting and the outcome of a general election, vis-a-vis a case study on the 14th Malaysian General Election 2018. Latest estimate from TI indicates that the amount of economic losses due to bribery in government procurement worldwide which includes allocation for national general election is at least USD 400 billion per year. For corrupt politicians, staying in power by subverting the democratic election process is a mean of perpetuating their corrupt practices and preventing or escaping from criminal investigations and persecutions.